Estradiol Aggravate Nocardia farcinica Infections in Mice - Han, Lichao; Ji, Xingzhao; Liu, Xueping; Xu, Shuai; Li, Fang; Che, Yanlin; Qiu, Xiaotong; Sun, Lina; Li, Zhenjun (Frontiers in Immunology, 2022)
Males are generally more susceptible to Nocardia infection than females, with a male-to-female ratio of 2 and higher clinical disease. 17β-Estradiol has been implicated in affecting the sex-based gap by inhibiting the growth of N. brasiliensis in experiments, but the underlying mechanisms have not yet been fully clarified. In the present study, however, we report increased severity in N. farcinica IFM 10152-infected female mice compared with male mice with increased mortality, elevated lung bacterial loads and an exaggerated pulmonary inflammatory response, which was mimicked in ovariectomized female mice supplemented with E2. Similarly, the overwhelming increase in bacterial loads was also evident in E2-treated host cells, which were associated with downregulating the phosphorylation level of the MAPK pathway by binding the estrogen receptor. We conclude that although there are more clinical cases of Nocardia infection in males, estrogen promotes the survival of the bacteria, which leads to aggravated inflammation in females. Our data emphasize the need to include and separately analyze both sexes in future studies of Nocardia to understand the sex differences in immune responses and disease pathogenesis.